2019
DOI: 10.1177/0163443719831181
|View full text |Cite
|
Sign up to set email alerts
|

Studying theNordic Resistance Movement: three urgent questions for researchers of contemporary neo-Nazis and their media practices

Abstract: This commentary provides critical reflections on a number of challenges related to research methodology and ethics when studying organized racism in online environments. Based on ongoing fieldwork of the Nordic Resistance Movement (NMR) in Sweden, I ask three critical questions about researching the neo-Nazi organization and organized racism more generally: (1) How do we produce valid knowledge of these ‘closed’ groups in their ‘open’ online spaces? What are the limitations of our research on hidden social lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
2
25
0
2
Order By: Relevance
“…Despite their increasing importance, research on RNS is still quite sparse. A number of studies have focused on related aspects, such as the spread of disinformation and fake news (e.g., Fletcher et al, ), extreme‐right groups’ use of the Internet (e.g., Askanius, ; Caiani & Kröll, ; Simpson & Druxes, ), and media populism (Krämer, , ). However, only a few studies have analyzed hyperpartisan alternative media outlets and their critical role in the emergence of digital news infrastructures.…”
Section: Studying Right‐wing Alternative Online News Mediamentioning
confidence: 99%
“…Despite their increasing importance, research on RNS is still quite sparse. A number of studies have focused on related aspects, such as the spread of disinformation and fake news (e.g., Fletcher et al, ), extreme‐right groups’ use of the Internet (e.g., Askanius, ; Caiani & Kröll, ; Simpson & Druxes, ), and media populism (Krämer, , ). However, only a few studies have analyzed hyperpartisan alternative media outlets and their critical role in the emergence of digital news infrastructures.…”
Section: Studying Right‐wing Alternative Online News Mediamentioning
confidence: 99%
“…This brings the benefit of, as Hammersley and Atkinson has it, 'living simultaneously in two worlds, that of participation and that of research' (Hammersley & Atkinson, 2007, p. 89). Moreover, in the case of working in disagreeable social fringes, such as the white radical-nationalist milieu, the podcast ethnographer has valuable opportunities to distancing and thus for coping with the 'emotional labour' required by this sort of field work (Askanius, 2019). Finally, we should note that podcast ethnography is a novel method that indeed needs further exploration -and a good deal of critical appraisal -in order to establish itself alongside the sibling methods of online ethnography.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…However, it has conversely been suggested that podcasts are rather 'complex multimodal texts' (Vasquez, 2013, p. 240), distinguishable from traditional radio due to the 'hyper-intimacy' of close and active listening to people from one's own community or specific sphere of interest (Berry, 2016, p. 667;Carlton, 2018). Podcasts can therefore be fruitfully studied in-depth to capture how interaction between the podcast speakers (re-)produces a particular universe (Askanius 2019;Nilsson 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative content analysis draws on empirical materials that have been purposely selected from the extensive database of digital content collected during an intensive period of online ethnographic fieldwork in 2018 comprising more than 1000 items (images, videos, memes, articles, speeches, manifests, podcasts) and field notes covering the broader time period of 2015-2018 (see Tina Askanius 2019). The analytical process unfolded across several stages of mining the data for themes and patterns across the dataset.…”
Section: Methodsmentioning
confidence: 99%